Are there opportunities for a closer collaboration on clinical stroke research in Europe?. (March 2018) - Berge, Eivind; Ford, Gary A.; Stapf, Christian; Al-Shahi Salman, Rustam; Fischer, Urs; Coveney, Sarah; Weimar, Christian; Arnold, Marcel; Arsovska, Anita; Lemmens, Robin; Nederkoorn, Paul J.; Kelly, Peter J.
Introduction: One of the aims of the European Stroke Organisation (ESO) is to facilitate academic, multinational clinical stroke research. However, despite examples of successful regional and national stroke research networks and collaborative groups, there is no organisational structure at a European level that can facilitate multinational clinical stroke research. Materials and methods: In a project including a survey and a workshop and involving stroke researchers in the ESO, we sought to identify the challenges faced by existing clinical stroke research networks, to define the purpose and roles of any future European stroke research collaboration, and to propose an organisational structure. Results: The survey and workshop gave strong support for an alliance model with independent network members, with the purpose of facilitating clinical stroke research through improved coordination and communication, provision of support, education, and advocacy and communication with other stakeholders. The focus of a proposed European clinical stroke research alliance should be multinational randomised-controlled trials in acute care, prevention and rehabilitation, but the alliance could also support other forms of multi-national clinical stroke research. Conclusion: There is an interest for increased collaboration on multinational clinical stroke research in Europe, in the form of an alliance of independent research networks and collaborative groups. The ESO Trials Network Committee will continue consultation with existing stroke research networks and collaborative groups, and other key stakeholders, to assess the feasibility and support for development of an ESO Trials Alliance.